Regional variations of credits obtained by LEED 2009 Certified green buildings-A country level analysis - Wu, Peng; Song, Y.; Wang, J.; Wang, X.; Zhao, X.; He, Q. (M D P I AG, 2017)
© 2017 by the authors. Leadership in Energy and Environmental Design (LEED) is one of the most widely recognized green building rating systems. With more than 20% of the projects certified in non-United States (US) countries, LEED's global impact has been increasing and it is critically important for developers and regulatory authorities to understand LEED's performance at the country level to facilitate global implementation. This study therefore aims to in vestigate the credit achievement pattern of LEED 2009, which is one of the well-developed versions of LEED, by using 4021 certified projects in the US, China, Turkey, and Brazil. The results show that significant differences can be identified on most rating categories, including sustainable sites, water efficiency, energy and atmosphere, indoor environmental quality, and innovation in design. Using a post hoc analysis, country-specific credit allocation patterns are also identified to help developers to understand existing country-specific green building practices. In addition, it is also found that there is unbalanced achievement of regional priority credits. The study offers a useful reference and benchmark for international developers and contractors to understand the regional variations of LEED 2009 and for regulatory authorities, such as the U.S. Green Building Council, to improve the rating system, especially on designing regional priority credits.